2013
DOI: 10.1097/bsd.0b013e318236b92d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Discectomy in Octogenarian Patients With Lumbar Disc Herniation

Abstract: Discectomy through hemilaminectomy is a feasible, safe, and effective treatment procedure in octogenarian patients with lumbar disc herniation. Disc resection in octogenarian patients usually gives good or excellent results. Careful examination of the surgical indications and attentive perioperative management should be considered for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…12,17 Zheng and colleagues used multivariate analysis to study 112 patients who underwent revision posterior lumbar fusion between 1992 and 1999 and found that increasing age was the only significant predictor of a longer hospital stay. 17 A more recent study by Nie et al reports differences in LOS between age groups after lumbar discectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,17 Zheng and colleagues used multivariate analysis to study 112 patients who underwent revision posterior lumbar fusion between 1992 and 1999 and found that increasing age was the only significant predictor of a longer hospital stay. 17 A more recent study by Nie et al reports differences in LOS between age groups after lumbar discectomy.…”
Section: Discussionmentioning
confidence: 99%
“…17 A more recent study by Nie et al reports differences in LOS between age groups after lumbar discectomy. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have sought to identify factors that affect LOS associated with ASD surgical intervention: Hassanzadeh et al 10 reported no significant differences in duration of hospitalization between ASD surgical patients who underwent primary or revision surgery; McCarthy et al 9 found that mean LOS for ASD patients with primary idiopathic scoliosis was lower than for patients with primary degenerative scoliosis, primary sagittal plane deformity, and patients who underwent revision surgery. Individual risk factors for extended LOS have also been characterized in the context of spine surgery: morbid obesity, 11 age, 12 and minimally invasive surgery (MIS) versus open surgical approach. 13 However, results regarding LOS and spine surgery have predominantly been those of incidence; an analysis evaluating length of stay as an isolated outcome measure is lacking.…”
mentioning
confidence: 99%
“…2–5 Several studies have demonstrated an increase in lumbar surgical intervention (decompression and/or fusion) in the broadly termed elderly population over the past 20 years. 2,3,68 Other studies have investigated safety and efficacy of lumbar spine surgery in this age group, with results showing both benefits 913 and risks. 14 However, no prior study has specifically identified national trends in the use of lumbar fusion surgery for the octogenarian population, with respect to demographics, discharge time, and economic impact.…”
Section: Introductionmentioning
confidence: 99%